Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

marixoxo76

  • 3 years ago

Solve. (x-16)-(2x-7)=1

  • This Question is Closed
  1. AndAntez
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Distribute the negative to both 2x and -7 which then gives you -2x and positive 7. Then combine like terms (-16 and 7, -2x and x). Get x alone afterwards

  2. rosedewittbukater
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    -x -9 = 1 -x = 10 x = 10

  3. rosedewittbukater
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    I subtracted the like terms (x-2x) = -x and (-16-(-7)) = -16+7 = 9 to get -x -9 =1 then I added 9 to both sides to get x by itself -x = 10 and finally divided both sides by -1 so x = 10

  4. marixoxo76
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Thank you

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy